2010
DOI: 10.1097/iae.0b013e3181bd2f94
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography-Raster Scanning and Manual Segmentation in Determining Drusen Volume in Age-Related Macular Degeneration

Abstract: Drusen volume as determined by spectral domain-OCT correlates with AREDS-determined drusen area and AREDS grade in nonexudative AMD. The correlation is not perfect, however, because drusen area and volume average 40% and 82% of the variation, respectively. Drusen volume can provide additional information in grading the severity of eyes with dry AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 21 publications
2
62
0
2
Order By: Relevance
“…133 Using higher-quality images compared with the original Rodenstock SLO, the investigation of retinal sensitivity in the junctional zone of patients with atrophic AMD using OCT/SLO MP was repeated. 96 Similar to the original report, findings of variable but definite reduction in retinal sensitivity was noted in patients with increased FAF intensity in the junctional zone. RPE cell damage in the regions characterized by increased FAF was also confirmed by SD-OCT imaging.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…133 Using higher-quality images compared with the original Rodenstock SLO, the investigation of retinal sensitivity in the junctional zone of patients with atrophic AMD using OCT/SLO MP was repeated. 96 Similar to the original report, findings of variable but definite reduction in retinal sensitivity was noted in patients with increased FAF intensity in the junctional zone. RPE cell damage in the regions characterized by increased FAF was also confirmed by SD-OCT imaging.…”
supporting
confidence: 74%
“…96,102,125 Prior to this, MP layer. 127 The relationship between the IS-OS layer and retinal sensitivity has been reported in a variety of diseases.…”
Section: Microperimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…13 Spectral-domain OCT (SD-OCT) has been demonstrated as a useful technique in the characterization of AMD. [14][15][16] Previous investigations of the relationship between these structural and functional measures in patients with early and late AMD, using SLO microperimetry combined with SD-OCT, have shown significant correlations between retinal sensitivity and drusen volume 11 and between sensitivity and integrity of the inner segment/outer segment junction 11,17 (herein called the inner segment ellipsoid [ISe] band 18 ). Another study described an association between retinal thinning and rod-mediated light sensitivity in nonexudative AMD.…”
Section: Resultsmentioning
confidence: 99%
“…High-quality individual B-scans are able to show fine details of drusen structure and morphology 18 and estimate damage to the photoreceptor layer over the drusen. 19 Furthermore, recent studies have shown the potential of SD-OCT to quantify geometrical parameters of the RPE deformations typically associated with drusen, using manual measurement of drusen volume, 20 semiautomatic measurement of drusen area and drusen size, 21,22 and automatic detection and measurement of drusen area, height, and volume. [23][24][25][26][27] To better understand the relationship between drusen defined as pigmentary changes on fundus photography and drusen defined in terms of RPE geometry, we compared the area measurements obtained using both imaging modalities.…”
mentioning
confidence: 99%